ARTRITIS SÉPTICA POR STREPTOCOCCUS EQUI: REPORTE DE UN CASO Y REVISIÓN DE LA LITERATURA - Lina María Echeverri-Toro (Asociación Colombiana de Infectología, 2019)
Human infections caused by Streptococcus equi are rare, have a wide variety of forms of presentation, including joint involvement, which has been rarely described in humans and even less in immunocompetent patients. In this article we present a septic arthritis case due to S. equi that occurred due to an occupational exposure in an immunocompetent patient, and a review of the related literature as well. The publication of this case report was accepted by the institutional ethics committee and the consent signed by the patient was obtained.